Comparing Population-General and Sport-Specific Correlates of Disordered Eating Amongst Elite Athletes: A Cross-Sectional Study - Scott J. Fatt; Emma George; Phillipa Hay; Nikki Jeacocke; Deborah Mitchison (Sports Medicine - Open)
Abstract Background Despite the high prevalence of disordered eating and eating disorders amongst elite athletes, it remains unclear whether risk factors and psychological processes align with those in the general population or if there are unique sport-factors associated with heightened risk. This cross-sectional study investigated if sport-specific factors (including pressures and psychological processes) explained additional variance in elite athletes’ disordered eating symptoms, controlling for established population-general risk factors. Current elite athletes (N = 178, 72.4% female, mean age = 23.9, standard deviation age = 7.0) completed online surveys assessing disordered eating, body dissatisfaction, perfectionistic traits, population-general and sport-specific pressures, as well as general (thin-ideal, muscular-ideal) and athlete-specific (drive for leanness for performance, athletic identity) psychological processes. Results Disordered eating was highly prevalent, with 78.2% of athletes reporting at least moderate risk, 46.4% at least high risk, and 20.6% very high risk. Controlling for demographic covariates and population-general pressures, sport-specific pressures explained significant additional variance (13.5%) in disordered eating. Even when controlling for perfectionistic traits, greater weight pressures in sport (β = .35) was uniquely associated with greater disordered eating. In a separate multivariate analysis controlling for covariates and general psychological processes, athlete-specific psychological processes explained significant additional variance (15.5%) in disordered eating. Even when controlling for body dissatisfaction, greater drive for leanness for performance (β = .17) and athletic identity (β = .13) were uniquely associated with greater disordered eating. Conclusions These findings support evidence that elite athletes may experience dual pressures and psychological processes associated with disordered eating: those congruent with appearance-oriented models and others independent of appearance. This duality should be considered in the modification of interventions for disordered eating in elite athletes. Key points 1. Disordered eating was highly prevalent in a sample of 178 elite adult athletes, with 78.2% reporting at least moderate risk for having related symptoms or behaviours. 2. Greater weight pressures in sport was significantly associated with greater disordered eating, even when controlling for demographic covariates and population-general appearance-related pressures from family and the media. 3. Both appearance-based (drive for thinness, body dissatisfaction) and non-appearance (drive for leanness for performance, athletic identity) psychological processes were uniquely associated with greater disordered eating.